Effect of single caffeine intake on neuropsychological functions in healthy volunteers: A double-blind placebo-controlled study. - Yuki Konishi; Hikaru Hori; Kenta Ide; Asuka Katsuki; Kiyokazu Atake; Ryohei Igata; Takamitsu Kubo; Hirotaka Tominaga; Hiroki Beppu; Toshio Asahara; Reiji Yoshimura (PLoS ONE, 2018)
OBJECTIVE:We investigated the effects of a single instance of caffeine intake on neurocognitive functions and driving performance in healthy subjects using an established cognitive battery and a driving simulator system. METHODS:This study was conducted in a double-blind, randomized, placebo-controlled manner from February 19, 2016 to August 6, 2016. Caffeine intake was discontinued 3 days prior to the study. Participants were randomly assigned to receive 200-mg doses of caffeine or a placebo. Thirty minutes after administration, cognitive functions were evaluated via the Symbol Digit Coding Test (SDC), the Stroop Test (ST), the Shifting Attention Test (SAT) and the Four Part Continuous Performance Test (FPCPT). After the cognitive function tests were conducted, driving performance was evaluated using a driving simulator. We measured the brake reaction time (BRT) in the Harsh-braking test and the standard deviation of the lateral position (SDLP) in the Road-tracking test. RESULTS:Of 100 randomized subjects, 50 (50%) of 100 in the caffeine group and 50 (50%) of 100 in the placebo group completed the study. Participants in the caffeine group had more correct responses than participants in the placebo group on the SAT (P = 0.03) and made fewer errors (P = 0.02). Participants in the caffeine group exhibited shorter times in the Harsh-braking test than participants in the placebo group (P = 0.048). CONCLUSIONS:A single instance of caffeine intake changed some neurocognitive functions and driving performance in healthy volunteers. TRIAL REGISTRATION:UMIN000023576.